2016
DOI: 10.1152/japplphysiol.00416.2015
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric contraction-induced myofiber growth in tumor-bearing mice

Abstract: Cancer cachexia is characterized by the progressive loss of skeletal muscle mass. While mouse skeletal muscle's response to an acute bout of stimulated low-frequency concentric muscle contractions is disrupted by cachexia, gaps remain in our understanding of cachexia's effects on eccentric contraction-induced muscle growth. The purpose of this study was to determine whether repeated bouts of stimulated high-frequency eccentric muscle contractions [high-frequency electrical muscle stimulation (HFES)] could stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 63 publications
3
72
0
Order By: Relevance
“…Sections were stained with hematoxylin and eosin according to a previous study [22, 23]. Fibers were analyzed by ImageJ 1.48v (National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sections were stained with hematoxylin and eosin according to a previous study [22, 23]. Fibers were analyzed by ImageJ 1.48v (National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…skeletal muscle metabolic dysfunction in both humans (Marzetti et al, 2017;Merlini, Bonaldo, & Marzetti, 2015) and murine models of cancer-induced wasting (Boland, Chourasia, & Macleod, 2013;Brown et al, 2017;Carson et al, 2016;Hardee et al, 2016). We have previously shown that 2 weeks of elevated circulating IL-6 decreased murine skeletal muscle mitochondrial protein expression, and loss of muscle gp130 signalling increased mitochondrial fission and reduced mitochondrial fusion in basal conditions Puppa et al, 2012Puppa et al, , 2014.…”
Section: New Findingsmentioning
confidence: 99%
“…Systemic overexpression of IL‐6 can accelerate the loss of muscle mass in tumour‐bearing mice, but the effects of IL‐6 on skeletal muscle mass and function in tumour‐free mice remain inconclusive (Puppa et al., ; White et al., , ). Mitochondrial function has emerged as an intriguing regulator of inflammation‐induced skeletal muscle metabolic dysfunction in both humans (Marzetti et al., ; Merlini, Bonaldo, & Marzetti, ) and murine models of cancer‐induced wasting (Boland, Chourasia, & Macleod, ; Brown et al., ; Carson et al., ; Hardee et al., ). We have previously shown that 2 weeks of elevated circulating IL‐6 decreased murine skeletal muscle mitochondrial protein expression, and loss of muscle gp130 signalling increased mitochondrial fission and reduced mitochondrial fusion in basal conditions (Fix et al., ; Puppa et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…There is clear evidence that hindlimb myofibers from tumor bearing rodents undergo atrophy regardless of the succinate dehydrogenase activity level [26,36,37,49] . Regardless, mitochondria dysfunction is an established regulator of myofiber protein turnover [21,25] , and gaps remain in our understanding of whether the fiber metabolic phenotype can produce differential regulation of cellular muscle wasting processes.…”
Section: Skeletal Muscle Oxidative Metabolism and Cancer Cachexiamentioning
confidence: 99%